Distal femur nonunion treated with retrograde intramedullary nailing and RIA: a case report - Pogliacomi, Francesco; Artoni, Carlotta; Calderazzi, Filippo; Leigheb, Massimiliano; Primiceri, Paolo; Pedrazzini, Alessio; Ceccarelli, Francesco; Vaienti, Enrico (Acta Biomedica Atenei Parmensis, 2020)
The current treatment of distal femur fractures includes locking plating and retrograde intramedullarynailing. These fractures are difficult to manage also for experienced surgeons, with results not alwayssatisfactory. Reported nonunion rates now range from 0 to 34%. Factors associated with nonunion includecomorbidities, such as obesity and diabetes, as well as the presence of open fractures, medial bone defectsand comminuted fractures. This case report summarizes all of these assumptions and it concerns a 58 yearsold patient who underwent to 6 surgical procedures before to arrive to bone healing.